2021
DOI: 10.1124/jpet.120.000373
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Throughput Concentration-Response Analysis of Human Taste Discrimination

Abstract: Human taste threshold measurements often are used to infer tastant receptor functionality.However, taste thresholds can be influenced by receptor-independent variables. Examination of the full range of taste-active concentrations by taste discrimination has been hampered by logistics of testing multiple concentrations in replicate with human subjects. We developed an automated rapid throughput operant methodology for taste discrimination and applied it to concentration-response analysis of human taste. Tastant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Further, we calculated the area under the curve (AUC) in Figure B to obtain the energy of oscillations stimulated and drew the dose-dependent curve, as shown in Figure D. According to the nonlinear regression analysis, the fitting curve was in good agreement with the theoretical psychophysiological curve of the taste system, and the EC50 was calculated to be 1.41% (41 mM), which agreed with the results obtained from the sensory evaluation …”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Further, we calculated the area under the curve (AUC) in Figure B to obtain the energy of oscillations stimulated and drew the dose-dependent curve, as shown in Figure D. According to the nonlinear regression analysis, the fitting curve was in good agreement with the theoretical psychophysiological curve of the taste system, and the EC50 was calculated to be 1.41% (41 mM), which agreed with the results obtained from the sensory evaluation …”
Section: Resultssupporting
confidence: 76%
“…Cooperativity as indicated could result from agonist–receptor interactions. After the acceleration, taste discrimination concentration–response functions for sucrose and citric acid are all saturated, as would be expected of a receptor-mediated process …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Effects were dose-dependent and could not be detected on the parental cell lines at concentrations up to 1–2 mM. EC 50 values confirmed that, overall, agonists activated the sweet taste receptor with the expected rank order of potency based on human taste data ( Schiffman and Gatlin, 1993 ; Li and Servant, 2008 ; Palmer et al, 2021 ). At concentrations ≥3 mM, we could detect receptor independent positive DMR responses.…”
Section: Discussionmentioning
confidence: 61%
“…Measured taste sensitivity tends to be higher with larger volumes, though this effect is relatively small and most pronounced at volumes substantially less than 1 ml (O'Mahony et al 1982;O'Mahony et al 1984, Brosvic andMcLaughlin 1989). Furthermore, reliable taste judgments are possible even with a small fraction of 1 ml (Colvin et al 2018;Palmer et al 2021). However, the effect of volume on judgments of retronasal aroma have not been explored as thoroughly, so some results might differ if more natural volumes were used.…”
Section: Limitationsmentioning
confidence: 99%